Cycle Relations: A proposed-CSR Model to Increase University s Intake - Wijaya, Lina Sinatra; Krismiyati, Krismiyati (Universitas Semarang, 2020)
Most higher education institutions in Central Java, especially in Salatiga have done some Corporate Social Responsibility (CSR) programs to achieve their goal which is increasing their intake yearly. This is a descriptive qualitative research which tries to investigate the implementation of CSR model proposed named Cycle Relations in one academic year. Interview and literature study are used to gain the data, and then analyzed qualitatively. 7 higher education institutions in Salatiga-Central Java and also 19 high schools which are spread in 7 cities in Central Java are used in this study. The reason why these institutions were involved was that this study was a continuation from a previous study. This result shows that indeed the CSR program the insitutions carried out impact towards their intake either directly or indirectly. The study indicates that those higher educations have done their Listen and Respond to create their sustainable CSR program.